Effectiveness of Constructed Wetland with a Variety of Plants in Processing Nickel Mining Waste - Lionie Lionie; Bieby Voijant Tangahu; Umar Kasmon (International Journal of Science and Environment (IJSE), 2026)
This study evaluates a pilot-scale constructed wetland for treating nickel mine wastewater from Watulabu Pond using combinations of Phragmites australis, Typha latifolia, and Chrysopogon zizanioides grown on topsoil and nickel slag–amended substrates. A mixed quantitative–qualitative approach was applied to assess technical performance (removal of TSS, Ni, and Cr⁶⁺), economic feasibility (operational costs relative to chemical treatment), and alignment with Indonesian environmental regulations for the nickel mining sector. All three macrophytes acclimatized well to nickel‑rich wastewater, but vetiver grass showed the strongest physiological response, with the highest plant height growth rate (1.00 cm/day) and vigorous tiller formation during 14 days of operation. Initial Cr⁶⁺ and total Cr concentrations of 1.73 mg/L and 1.99 mg/L (approximately 17× and 4× above national standards) were substantially reduced, with vetiver lowering Cr⁶⁺ and total Cr to 0.07 mg/L and 0.18 mg/L, respectively, both below discharge limits. TSS decreased from 350 mg/L to as low as 4.5–8.0 mg/L in topsoil‑based systems, corresponding to removal efficiencies up to 98.31%, while Fe and Ni removals consistently exceeded 90% in vegetated reactors. Vetiver achieved the highest metal removal efficiencies (Cr⁶⁺ 96.19%, total Cr 90.98%, total Fe 95.84%, total Ni 96.02%) and the greatest removal rates (0.111 mg/L/day for Cr⁶⁺ and 0.121 mg/L/day for total Cr), supported by very high Bioconcentration Factor values for total Cr (7,272.87) and Cr⁶⁺ (134.37), indicating exceptional root accumulation. In contrast, nickel slag–amended media showed lower accumulation capacity and, in some cases, negative removal for Cr species, suggesting chromium leaching and confirming pure topsoil as the more suitable substrate. Operational cost analysis revealed that the constructed wetland reduced treatment costs from IDR 2,300 to IDR 750 per m³ (≈67% savings) compared with manual chemical dosing, while producing effluents that meet national standards for TSS, Ni, and Cr in the best configurations. Overall, the findings demonstrate that appropriately designed constructed wetlands—particularly those using vetiver on topsoil—can simultaneously achieve high removal of Cr⁶⁺, Ni, Fe, and TSS, lower operating costs, and improve regulatory compliance, offering a technically robust and economically attractive option for sustainable nickel mine wastewater management in Indonesia.